Mediating role of coping style on the relationship between job stress and subjective well-being among Korean police officers - Gi Wook Ryu; Yong Sook Yang; Mona Choi (BMC, 2020)
Abstract Background Police officers have long been known to have one of the most stressful occupations. This study investigates their stress levels, coping styles, and subjective well-being, including affect and life satisfaction. We also explore the interrelationships of these factors to determine how coping style influences a police officer's subjective well-being. Methods We used a convenience sampling method for 112 police officers in a metropolitan area in South Korea. Data were collected using self-administered questionnaires. The questionnaires consisted of the following scales: job stress, coping style, positive/negative affect, and life satisfaction that measured subjective well-being. Descriptive statistics, a correlation analysis and Hayes' PROCESS macro, and bootstrap analysis were performed. Results The level of job stress for the participants was moderate, with an average of 43.57 out of 100. The mean scores of positive affect was 17.38 out of 40, 8.50 out of 40 for negative affect, and 20.76 out of 35 for life satisfaction. Job stress and coping were significantly correlated with subjective well-being, and problem-solving style mediated stress, positive affect, and life satisfaction. Lastly, assistance pursuit style mediated stress and positive affect. Conclusions Participants' problem-solving and assistance pursuit coping styles were shown as important mediating factors for stress and subjective well-being, especially positive affect. These findings need to be considered when planning interventions and implementing strategies focusing on the psychosocial health of the improvement of police officers' well-being.